The Effect of Corporate Governance, Leverage, and Firm Size on Financial Distress - Vera Fiyanti; Harti Budi Yanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to analyze the effect of corporate governance, leverage and firm size on financial distress. The population in this study was 652 consumer cyclicals and non-consumer cyclicals companies listed on the Indonesia Stock Exchange for the 2020-2023 period. This sample research used a purposive sampling method and obtained a sample of 163 companies. The research results show that Firm Size has significant negative effect on financial distress, Leverage and corporate governance have no effect on financial distress.